Natural and anthropogenic sources of salinity in the Awash River and Lake Beseka (Ethiopia): modelling impacts of climate change and lake-river interactions - Jin, L.; Whitehead, P.G.; Bussi, G.; Hirpa, F.; Taye, Meron Teferi; Abebe, Y.; Charles, K. (Elsevier, 2021)
Study region: Awash River Basin, Ethiopia: Study focus: Many river basins in sub-Saharan Africa have become vulnerable due to the impact from climate change, weak governance and high levels of poverty. One of the primary concerns is the elevated salinity and the degradation of water quality in the Awash River. Located in the Great Rift Valley in Ethiopia, the Awash River has unique hydrochemistry due to water-rock interactions. However, in recent years, increasing anthropogenic activities including the discharge from saline Lake Beseka into the Awash River has caused some concern. This study used an Integrated Catchment Model to simulate chloride concentration in the Awash River Basin by taking both natural and anthropogenic sources of salinity into consideration. Future scenarios of climate change and Lake Beseka discharge were examined to assess the impact to the river water quality. New hydrologic insights: Results show that Lake Beseka has made significant contribution to the rise of the salinity in the Awash River. If the trend of human interference (e.g. increased irrigation and unregulated water transfer) continues, the river downstream of Lake Beseka could see Cl increases up to 200 % in the near future (2006–2030). The modeling results are essential for generating long term plans for proper utilization of water resources especially in the region where the resources and the economic capacity to meet the water demand is lacking.